Performing deviance in front stage spaces: Prince Roger Nelson and the boundary fluidity of masculinity - Gay, Tyler (Deviant behavior, 2021)
The music entertainment industry is very influential in creating/extending conversation around social issues and controversies. This paper examines the influence that musicians have over the understanding of gender norms and queerness. Specifically, this paper will highlight the musician by the name of Prince. His reign of funk and sensuality challenged the view of gender and sexuality; the coupling of masculinity and queerness. Three areas of Prince will be examined for evidence of queerness: physical appearance, song, and performance. The fluid stage set for prince’s masculinity boundary challenge will also be discussed.